Maternal health-related barriers and the potentials of mobile health technologies: Qualitative findings from a pilot randomized controlled trial in rural Southwestern Uganda - Tumuhimbise, Wilson (J Family Med Prim Care, 2020)
BACKGROUND: Maternal mortality rate remains unacceptably high in Uganda. In-depth evidence about the barriers to access and utilization of maternal health services specifically among the rural illiterate pregnant women remains lacking. The potentials of mobile health technologies in addressing the maternal health challenges remain unclear. AIM: To explore the maternal health-related barriers among illiterate pregnant women in rural Southwestern Uganda and highlight the potentials of mobile health technologies. MATERIAL AND METHODS: This is a midline qualitative study conducted with the participants of a pilot randomized controlled trial. Between October 2019 and December 2019, we carried out semi-structured interviews with 30 illiterate pregnant mothers. Interviews elicited information on the barriers to access and utilization of maternal health services. An inductive, content analytic approach was used to analyze qualitative data. Quantitative sociodemographic and socioeconomic data were summarized descriptively. RESULTS: Participants reported that lack of money (for transport and medical costs), unfriendly maternal health services, and delays at the maternal health clinic constrain access and utilization of maternal health services. Given their widespread adoption, mobile technologies can potentially address some of these barriers e.g., money for transport or microenterprise start-up can be sent to women through their mobile phones or maternal health-related services (such as health education and consultation) can be provided electronically. CONCLUSION: Future efforts should focus on utilizing mobile health technologies to not only enable women overcome the critical financial challenges but also facilitate remote access and utilization of maternal health services.